Hotel ammenities, customer satisfaction and customer experience: a test of mediation/ Faizal Azrin Abdullah, Tuan Ahmad Tuan Ismail and Abdullah Muhamed Yusoff - Abdullah, Faizal Azrin; Tuan Ismail, Tuan Ahmad; Muhamed Yusoff, Abdullah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Optimistic service experience, with its final effect on revisiting and repurchasing by customers, it appears to have gained little attention. This study starts by first outlining the concept of service experience and proceeds to differentiate between hotel amenities and customer satisfaction. The survey included 300 people who stayed at Malaysian three-star hotel. In a structured questionnaire, a five-point Likert scale was used. The unidirectional correlations between hotel room amenities, customer satisfaction, and customer experience were investigated using SPSS, as well as predictions about model construct relationships were tested. A mediational model is proposed that connects hotel room amenities to customer satisfaction through the customer experience. Customer experience does mediate the effect of hotel room amenities on customer satisfaction, according to the findings. The study's implications are examined, as well as the study's recommendations and possible research fields.